Application of conveyor belt monitoring technology to conveyor belt reliability - J. L. Barton; R. A. Murray (Canadian Institute of Mining, Metallurgy and Petroleum, 1992)
"This paper looks at how Syncrude Canada Ltd. is utilizing the Conveyor Belt Monitoring technology developed and patented by the Australian CSIRO and licensed to Syncrude by Conveyor Belt Monitoring of North America, Inc. The technology involves magnetizing the steel cables in the conveyor belts and detecting the fields produced by breaks, gaps or cable ends using special sensors which feed the signals into a multi- channel recorder to provide permanent traces of the various events taking place in the steel cable belts.The data is analyzed and combined with existing belt audit programs, to assist in predicting belt life, change-out criteria and belt design, belt loading and construction. All of these applications of the CBM technology leads to better utilization of resources and forms an integral part of the conveying system reliability program."